Innovation diffusion in time and space: effects of social information and of income inequality - Kandler, Anne; Steele, James (Diffusion Fundamentals, 2009)
In this paper we consider the spread of modern technological innovations. We contrast social learning and threshold heterogeneity models of innovation diffusion, and show how the typical temporal evolution of the distribution of adopters may be consistent with either explanation. Noting the likelihood that each model contains some useful independent explanatory power, we introduce a combined model. We also consider a spatially-structured population in which the spread of an innovation by social influence is modelled as a reaction-diffusion system, and show that the typical spatiotemporal evolution of the distribution is also consistent with a heterogeneity explanation. Additional contextual information is required to estimate the relative importance of social learning and of economic inequalities in observed adoption lags.